The Algorithmic Gaze: Integrating AI into Prenatal Ultrasound for Enhanced Fetal Care - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The Algorithmic Gaze: Integrating AI into Prenatal Ultrasound for Enhanced Fetal Care The prenatal ultrasound examination stands as a cornerstone of mod...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning